Geochemistry of C enozoic volcanic rocks in T engchong, SW C hina: relationship with the uplift of the T ibetan P lateau - Yutao Zhang; Jiaqi Liu; Fanchao Meng (Island Arc, 2012)
There are wide spread C enozoic volcanic rocks in T engchong ( CVRT ), Y unnan province, SW C hina. These rocks comprise three rock types: basalt, andesite (dominant type) and dacite. Most samples are sub‐alkaline, and among the sub‐alkaline rocks, most are high‐ K calc‐alkaline. These rocks have a SiO 2 range of 49.1 wt.% to 66.9 wt.%. TiO 2 contents are not high and have a variation of 0.7 wt.%–1.6 wt.%. Trace element concentrations and element ratios (such as Nb / U , Ce / Pb , Nb / La , etc.) of these rocks have a large variation. 87 Sr / 86 Sr values fall in the range of 0.7057–0.7093 and 143 Nd / 144 Nd values change from 0.5120 to 0.5125. 206 Pb / 204 Pb , 207 Pb / 204 Pb , and 208 Pb / 204 Pb ratios are in the range of 17.936–19.039, 15.614–15.810, and 38.894–39.735, respectively. These geochemical characteristics of CVRT make them resemble island‐arc volcanic rocks. We suggest that the magmas were generated in the lithospheric mantle that had already been metasomatized by previous subduction processes. By the study of the uplift history of the Tibetan Plateau, we found that the beginning of the geotectonic processes to the eruption of CVRT was coeval with one uplift event. Therefore, we propose that the uplift of the Tibetan Plateau caused collapse of the collisional orogeny in Tengchong, which further triggered the generation and eruption of the CVRT magmas.